The NEUROGES® Analysis System for Nonverbal Behavior and Gesture The Complete Research Coding Manual including an Interactive Video Learning Tool and Coding Template - Lausberg, Hedda (Peter Lang International Academic Publishers, 2019)
The NEUROGES® analysis system is an objective and reliable interdisciplinary research tool for analysis of body movement and gesture. The system has been field-tested on more than 500 individuals from cultures of five continents, including healthy adults and children as well as individuals with mental illness or brain damage, and further, on non-human primates. Following up on the first book on theoretical background of the NEUROGES® system, which was published in 2013, this book contains the complete coding manual for the application of the system in research including an interactive video learning tool with video examples of all NEUROGES® hand movement and gesture types, training videos, and a template file for the Multimedia Annotator ELAN.